Integrated Hospital System Administration System / Ng Siao Wei - Ng , Siao Wei (2001)
The concept of Integrated Hospital System have been brought up to take advantage of the modern technologies; the tremendous growth of information technology has change the olden style of management into electronic based. Based on the objective, the system is build to substitute the manual process that is practiced in most of the hospital especially in government hospital now a day. It is aim to reduce the time spent from registration, help get pharmacy done quickly, helps to generate the bill faster and accurately and help people to get their information in their fingertips when and where they need it. The system have been divided into several sub system, which is the administration system, patient care services system, clinical care services system, emergency care services system. In this proposal, the development process of the Administration System will be elaborate in detail.